Infrared studies of ortho-para conversion at Cl-atom and H-atom impurity centers in cryogenic solid hydrogen - Raston*, P.L.; Kettwich, S.C.; Anderson, D.T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We report infrared spectroscopic studies of H2 ortho-para (o/p) conversion in solid hydrogen doped with Clatoms at 2 K while the Cl + H2(v = 1) → HCl + H infrared-induced chemical reaction is occurring. The Cl-atom doped hydrogen crystals are synthesized using 355 nm in situ photodissociation of Cl2 precursor molecules. For hydrogen solids with high ortho-H2 fractional concentrations (Xo = 0.55), the o/p conversion kinetics is dominated by Cl-atom catalyzed conversion with a catalyzed conversion rate constant Kcc = 1.16(11) min–1 and the process is rate-limited by ortho-H2 quantum diffusion. For hydrogen crystals with low ortho-H2 concentrations (Xo = 0.03), single-exponential decay of the ortho-H2 concentration with time is observed which is attributed to H-atom catalyzed o/p conversion by the H-atoms produced during the infrared-induced Cl + H2 reaction. The measured H-atom catalyzed o/p conversion kinetics indicates the H-atoms are mobile under these conditions in agreement with previous ESR measurements.